2016
DOI: 10.1590/1981-6723.0816
|View full text |Cite
|
Sign up to set email alerts
|

Saciedade subjetiva, aceitação sensorial e aspectos tecnológicos de salsicha com adição de fibra de trigo

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado.Saciedade subjetiva, aceitação sensorial e aspectos tecnológicos de salsicha com adição de fibra de trigo Subjective satiety, sensory acceptance and technological aspects of frankfurter sausage with added wheat fibre ResumoO objetivo deste trabalho foi a elaboração de salsichas com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
3
3
1
Order By: Relevance
“…There was a significant difference for the ash content (p < 0.05) between treatments where the contents varied between 3.25 and 3.45%. Similar values of ash content were described by Borrajo et al (2016) in sausages with added wheat fibre.…”
Section: Physicochemical Characterizationsupporting
confidence: 86%
See 2 more Smart Citations
“…There was a significant difference for the ash content (p < 0.05) between treatments where the contents varied between 3.25 and 3.45%. Similar values of ash content were described by Borrajo et al (2016) in sausages with added wheat fibre.…”
Section: Physicochemical Characterizationsupporting
confidence: 86%
“…Several studies have shown the possibility of replacing fat with dietary fibre in meat products with good sensory acceptance (Huang et al, 2011;Grizotto et al, 2012;Schmiele et al, 2015;Talukder, 2015;Barretto et al, 2015;Borrajo et al, 2016;Carvalho et al, 2017;Bis-Souza et al, 2018;Zhao et al, 2018;Abbasi et al, 2019), increasing the intake of this component in the diet. These ingredients can contribute giving technological benefits in meat products in order to improve their nutritional and sensory characteristics (Méndez-Zamora et al, 2015;Paglarini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples also showed no difference in ash content between the 1 st and the 10 th days of storage, with values varying from 2.87% to 3.05%. Ash results in the present study are like those observed by Borrajo et al (2016), who found values between 3.2% and 3.4% in a wheat fiber-enriched sausage.…”
Section: Physicochemical Characteristics Of Sausagessupporting
confidence: 91%
“…From the 1 st to the 10 th day of storage, there was a reduction between 0.53% and 0.59% in the lipid content of sausages, although this difference was not significant, either. Borrajo et al (2016) did not observe difference in lipid content of sausages with addition of wheat fiber, either. These results are different from the values found by Özvural et al (2009), who analyzed Frankfurters with addition of malt pomace, and found a lipid content of 15.92%, while the control formulation had a value of 18.05%.…”
Section: Physicochemical Characteristics Of Sausagescontrasting
confidence: 52%